Suppression of literal meanings in L2 idiom processing: Does context help? - Cieślicka, Anna, B. (Zakład Filologii Angielskiej: Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2011)
Most current idiom processing models acknowledge, after Gernsbacher and Robertson (1999) that deriving an idiomatic meaning entails suppression of contextually inappropriate, literal meanings of idiom constituent words. While embedding idioms in the rich disambiguating context can promote earlier suppression of incompatible literal meanings, idioms embedded in the neutral context, favoring neither their literal nor figurative reading, are likely to become disambiguated much later in the course of their comprehension. The study reported in this paper investigates the role of context in suppressing irrelevant, literal meanings of idioms in the course of their processing by Polish proficient speakers of English. Ambiguous (literally plausible) English idioms were embedded in sentences which were either neutral (i.e., did not bias either the literal or figurative reading of the idiom, e.g., There was no need to add fuel to the fire) or figurative-biased (e.g., The chairman is in a bad mood so do not say anything, as this will only add fuel to the fire) and followed by targets related literally (e.g., HEAT) or figuratively (e.g., WORSE) to idiom meanings and displayed either immediately at idiom offset (0 ms) or after 300 ms. The self-paced reading paradigm was employed, in which participants first read the idiomatic sentences at their own pace and then made a lexical decision, i.e., decided if the displayed target string is a legitimate English word or not. Context was shown to play an important role in suppressing irrelevant meanings, but its effects were modulated by salience (prominence) of idioms’ literal meanings as well as the time that elapsed from the end of the sentence to the display of the target stimulus.
Keywords: Second language; Idiom processing; Context; Salience; Suppression